CREATION OF AN INFORMATION SYSTEM FOR MANAGING THE ACTIVITIES OF TESTING LABORATORIES OF AN EXPERT INSTITUTION IN THE SPHERE OF MEDICINAL PRODUCTS CIRCULATION - K. А. Koshechkin (Регуляторные исследования и экспертиза лекарственных средств, 2018)
This article describes the results of Laboratory Information Management System implementation in an expert institution dealing with medicines evaluation. The purpose of the study was to evaluate the feasibility of providing digital support to the laboratories of the Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products» of the Ministry of Health of the Russian Federation and to assess the functionality of the information system in terms of coverage of functional capabilities of various classes of laboratory software. The implementation of laboratory automation systems is required by the current regulations and is in line with international approaches to organisation of the quality management. The information system implementation made it possible to computerize management of drug samples, distribution of assignments among responsible employees, storage and management of documents, and reporting of test results. It created opportunities for direct integration with laboratory equipment allowing for creation of analytical protocols without manual data transfer. The implemented solution meets all requirements and standards for the functional capabilities of laboratory information systems. A similar system could be used in chemical, pharmacological, medical and biochemical laboratories, its implementation will make it possible to meet both national and international standards. These innovations are part of the concept of CALS/PLM technologies integration into institutions management programmes.